Discovery of Small Anti‐ACE2 Peptides to Inhibit SARS‐CoV‐2 Infectivity. Issue 7 (26th April 2021) - Adhikary, Pratik; Kandel, Sashi; Mamani, Umar‐Farouk; Mustafa, Bahaa; Hao, Siyuan; Qiu, Jianming; Fetse, John; Liu, Yanli; Ibrahim, Nurudeen Mohammed; Li, Yongren; Lin, Chien‐Yu; Omoscharka, Evanthia; et al.
Abstract: COVID‐19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which infects host cells by binding its viral spike protein receptor‐binding domain (RBD) to the angiotensin converting enzyme 2 (ACE2) on host cells. Blocking the SARS‐CoV‐2‐RBD/ACE2 interaction is, therefore, a potential strategy to inhibit viral infections. Using a novel biopanning strategy, a small anti‐ACE2 peptide is discovered, which shows high affinity and specificity to human ACE2. It blocks not only the SARS‐CoV‐2‐RBD/ACE2 interaction but also the SARS‐CoV‐1‐RBD/ACE2 interaction. Moreover, it inhibits SARS‐CoV‐2 infection in Vero‐E6 cells. The peptide shows negligible cytotoxicity in Vero‐E6 cells and Huh7 cells. In vivo short‐term lung toxicity study also demonstrates a good safety of the peptide after intratracheal administration. The anti‐ACE2 peptide can be potentially used as a prophylactic or therapeutic agent for SARS‐CoV‐2 or other ACE2‐mediated viruses. The strategy used in this study also provides a fast‐track platform to discover other antiviral peptides, which will prepare the world for future pandemics. Abstract : Peptide therapeutics is gaining increased interest in recent years due to its high selectivity, efficacy, and tolerability. Small anti‐ACE2 peptides that can effectively block the SARS‐CoV‐2‐RBD/ACE2 interaction are discovered using peptide phage biopanning. These peptides show high affinity and specificity toward human ACE2 and are capable of inhibiting the SARS‐CoV‐2 infection. This strategy can be used as a fast‐track platform to discover other antiviral peptides.